2012
DOI: 10.1590/s0102-09352012000200036
|View full text |Cite
|
Sign up to set email alerts
|

Histological characteristics of the corpus luteum of Nelore cows in the first, second and third trimester of pregnancy

Abstract: Communication

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
2
8
0
1
Order By: Relevance
“…Comparing the histology of the CL in three trimesters of pregnancy (Xavier et al, 2012), reported that the morphometric characteristics of luteal steroidogenic cells did not change. However, by the end of pregnancy, there was an increase in connective tissue, the number of fibroblasts and extracellular matter, especially after 190 days of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparing the histology of the CL in three trimesters of pregnancy (Xavier et al, 2012), reported that the morphometric characteristics of luteal steroidogenic cells did not change. However, by the end of pregnancy, there was an increase in connective tissue, the number of fibroblasts and extracellular matter, especially after 190 days of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In cows, the CL is represented by granulose-luteal cells of large size and by small theka-luteal cells. Thekaluteal cells are located mainly peripherally; they penetrate the thickness of the CL together with connective tissue trabeculae (Cools et al, 2013b;Walusimbi and Pate, 2014;Xavier et al, 2012). In cows, luteal cells of "average size" are described; they are allocated to a special class with significant morphofunctional features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Esse resultado foi semelhante ao encontrado por Xavier et al (2012), que verificaram que esses grânulos estão presentes em maior quantidade ao final do segundo terço e durante o terceiro terço da gestação. A ausência de grânulos citoplasmáticos em células lúteas menores sugere que essas células apresentam menor atividade em relação as células maiores e talvez menor participação no processo de luteólise e na manutenção da gestação.…”
Section: Resultsunclassified